Uncovering Emerging Health Awareness Trends in Education: A Bibliometric Study - Iin Uswatun Hasanah; Jumadi Jumadi; Fauji Agusta; Rey Abraham; Siti Tsurayya Yaqutunnafis; Sri Bona Ayu (IJORER : International Journal of Recent Educational Research, 2025)
Objective: The study aims to examine the development of research trends related to health awareness in schools or education. Method: Data were obtained from the Scopus database and analyzed using PRISMA analysis, VOSviewer assistance, and bibliometric analysis. Results: A total of 182 relevant articles with the keywords "health awareness" and "school" or "school environment" in the category of English articles in 2020-2024 were collected. The database was analyzed and visualized using the VOSviewer application. The results of this study provide insight into the development of health awareness as a trend in education. Data was obtained in the form of 1)trends in health awareness in schools or education, 2)countries that influence health awareness in schools or education, and 3) keywords that often appear. The results of this study can be used as a foundation for future research to better understand health awareness as a trend in school or education. Novelty: The novelty of this study lies in integrating health awareness in education, giving rise to a new trend regarding health awareness in schools or education, and providing researchers with an overview of future research opportunities related to health awareness and education through bibliometric analysis.